The Role of Oxytocin in Autism Spectrum Disorders - Canitano, Roberto; Scandurra, Valeria (Current Psychopharmacology, 2012)
Autism Spectrum Disorders (ASD) are characterized by dysfunction in three core symptom domains: social impairments, communication impairments, and repetitive behaviours with restricted interests. Oxytocin (OXT) and the structurally similar peptide arginine vasopressin (AVP), may play a role in the etiology of these disorders, especially in the social difficulties domain. Oxytocin is involved in milk let-down and uterine contractions at a peripheral level, while in the brain it predominantly has a neuromodulatory function on affiliative and social behavior. Abnormalities of OXT in ASD are herein reviewed, using blood studies, neuroimaging, and translational research. Genetic abnormalities in OXT have also been consistently reported in ASD. Clinical trials with OXT are currently aimed at reducing social impairments and repetitive behaviours. Finally, the current limitations and prospects for the future of OXT treatment in ASD are discussed.
Keywords: arginine vasopressin